Utilization of magnetite-supported coal fly ash as an efficient adsorbent for Pb metal removal in aqueous environments - Nurmaya Arofah; Annisa Naila Izzati; Yusraini Dian Inayati Siregar; Yulyani Nur Azizah; Agus Rimus Liandi (Case Studies in Chemical and Environmental Engineering)
This study explores the use of waste coal fly ash supported with magnetite (FA/Fe3O4) as an environmentally friendly adsorbent for removing Pb metal from aqueous solutions. FA/Fe3O4 composites were synthesized using the ball mill method with varying ratios (9:1, 9:3, and 9:5). The FA/Fe3O4 sample with a 9:3 ratio exhibited the most promising characteristics, including a high surface area (4.878 m2/g), substantial pore volume (2.508 cc/g), large average pore diameter (3.060 nm), low crystallinity (12.98 %), small crystal size (28.41 nm), and non-uniform particle morphology (average size of 2.6 μm). Optimal conditions for Pb removal were achieved with the 9:3 adsorbent, showing 95.50 % adsorption efficiency at 30 mg adsorbent mass, 98.83 % efficiency at pH 4, and 99.45 % efficiency at a concentration of 25 ppm. These findings indicate that FA/Fe3O4 composites provide a highly efficient and straightforward method for Pb removal, offering significant practical value in environmental applications.